ASUHAN KEPERAWATAN DENGAN PENERAPAN TEKNIK AKUPRESUR/P6 DALAM MENGATASI NAUSEA PADA DYSPEPSIA - Sawitri, Siti Alifia; Gemini, Savitri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Dyspepsia is an upper gastrointestinal disorder characterized by epigastric discomfort, nausea, vomiting, and early satiety. The prevalence of dyspepsia is relatively high in several countries, including the United States (23–25.8%), India (30.4%), and China (23.3%). In Indonesia, the prevalence of dyspepsia reaches 40–50% of the population. One non-pharmacological approach to managing dyspepsia is acupressure therapy. Acupressure is an effective non-pharmacological intervention for reducing nausea by stimulating the autonomic nervous system and balancing the body’s energy. This study employed a descriptive case study method involving one patient (Mrs. A) with a medical diagnosis of dyspepsia and a nursing diagnosis of nausea at Harapan Bunda Hospital, Batam. The intervention consisted of acupressure therapy at the Pericardium (P6) point for three consecutive days, with a duration of two minutes per session prior to pharmacological therapy. Data were collected through observation of changes in the patient’s nausea intensity and physiological responses. After three days of acupressure therapy, the patient demonstrated a significant reduction in nausea complaints. On the first day, the patient experienced severe nausea with five episodes of vomiting; on the second day, nausea decreased without vomiting; and on the third day, the patient no longer experienced nausea. The patient’s general condition improved, appetite increased, and daily activities returned to normal. The application of acupressure therapy at the Pericardium (P6) point was proven to be effective in reducing the intensity of nausea in patients with dyspepsia. Stimulation of this point helps stabilize the autonomic nervous system and improve the flow of body energy, thereby suppressing stimulation of the vomiting center. Acupressure can be considered a safe and easily applied complementary non-pharmacological nursing intervention for managing nausea in patients with dyspepsia. Keywords: Dyspepsia; Nausea; Acupressure Technique; Pericardium (P6).